KEARIFAN LOKAL DI BALIK MITOS LEMBU PUTIH DI DESA TARO, GIANYAR - I.B.G. Pujaastawa (Environmental Research Center (PPLH) of Udayana University, 2013)
AbstractThe study tried to reveal the local wisdom which resided behind the myth of white ox atTaro village, Gianyar. According to conception of social confidence at Taro village, existencethe white ox in the village represent the holy animal owned by deity who protecting theirlife. On that account, the society always treat it very respectively and prohibiting to exploitit for secular purposes. The phenomenon tried to comprehended by using cultural materialismapproach to expose the rationality which hidden behind the myth of the white ox. Currently,according to view of cultural materialism, stated that behind the traditional societyconfidence system often there are rational logics as form of adaptation response to economicconditions and ecology faced. This study found that behind myth about the white ox in Tarovillage consisted economic benefit and ecology in the form of, (1) distribution of agriculturearea and fee for the who herds, (2) as mechanism of pest control and (3) as mechanism ofgenetic purification of the white ox as endemic animal.